Antimalarial, Anticancer, Antimicrobial Activities and Chemical Constituents of Essential oil from the Aerial Parts of Cyperus kyllingia Endl - Khamsan S. (2017)
The chemical constituents of the essential oil from Cyperus kyllingia Endl. were analyzed by a GC, GC-MS. Twenty-three compounds were identified, accounting for 93.75% of the total oil that consisted mainly of oxygenated sesquiterpenes (53.52%), particularly sesquiterpene hydrocarbons (38.97%), and carboxylic acid (1.26%). The most representative compounds were α-cadinol (19.32%), caryophyllene oxide (12.17%), α-muurolol (11.58%), α-humulene (9.85%), and α-atlantone (6.07%). The oil showed significant activities against Plasmodium falcipalum (K1, multi drug resistant strain) and NCI-H187 (Small Cell Lung Cancer) with the IC50 values of 7.52 and 7.72 μg/mL, respectively. The oil exhibited highly active against Staphylococcus aureus ATCC25923 and moderately active against Escherichia coli ATCC25922, Pseudomonas aeruginosa ATCC27553, Aspergillus flavus and Candida albicans. © Published 04 15/2011 EISSN: 1307-6167.